Addressing small-scale forestry informal markets through forest policy revision: A case study in Papua New Guinea. (November 2019) - Scudder, Micah G.; Baynes, Jack; Applegate, Grahame; Herbohn, John
Highlights: Existing forest polices/regulations are the cause of informal market activities. Immediate monetary needs are the primary incentive for most informal market participants. Current distribution of timber rents favours small-scale wood product manufacturers. Abstract: Informal markets for timber harvested from small-scale and community forests can be vital to the development of rural economies and the empowerment of communities in many tropical developing countries. However, legal status of these markets is often uncertain, and this can prevent smallholders accessing government support and gaining access to financing. In Papua New Guinea (PNG), knowledge about the small-scale forestry informal market is limited, since the government does not have the resources to track or regulate it. Casual observation suggests that the market is comprised of individuals or businesses using portable sawmills for the commercial production of rough-sawn lumber. We used a descriptive case study approach to understand the processes of the forest-based informal market and to determine if there are specific forest policy/regulation features that are leading to informal market activities. We found that the forest policies/regulations are driving participation in the informal market because of vague policy definitions and the existing timber harvest permits being more suited to industrial-scale harvests and inappropriate to the needs of small-scale forestry participants. The current distribution of forest resource rents in the informal market is skewed in favour of small-scale timber product manufacturers, resulting in the forest resource owners receiving an inequitable share of the timber value. We estimated that the log harvests occurring in the informal market could be in the order of 560, 000 cubic meters (m 3 ) annually, which is equivalent to 17% of PNG's log exports in 2017. The estimated size of this market highlights the large unmet economic potential occurring in the small-scale forestry sector. We recommend that the existing harvest regulations be revised to include a new small-scale harvest permit of 500 m 3 per site per annum, along with improved timber royalty rates for the resource owners. In addition, we recommend increased government support be provided through extension foresters to improve the sustainability and productivity of the small-scale forest products market.